Immunogenicity, Effectiveness, and Safety of Inactivated Virus (CoronaVac) Vaccine in a Two-Dose Primary Protocol and BNT162b2 Heterologous Booster in Brazil (Immunita-001): A One Year Period Follow Up Phase 4 Study - Grenfell, Rafaella F. Q.; Almeida, Nathalie B. F.; Filgueiras, Priscilla S.; Corsini, Camila A.; Gomes, Sarah V. C.; de Miranda, Daniel A. P.; Lourenço, Adelina J.; Martins-Filho, Olindo A.; de Oliveira, Jaquelline G.; Teixeira-Carvalho, Andrea; Campos, Guilherme R. F.; Nogueira, Mauricio L.; et al. (Frontiers in Immunology, 2022)
Background: Effective and safe vaccines against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are critical to controlling the COVID-19 pandemic and will remain the most important tool in limiting the spread of the virus long after the pandemic is over. Methods: We bring pioneering contributions on the maintenance of the immune response over a year on a real-life basis study in 1,587 individuals (18-90 yrs, median 39 yrs; 1,208 female/379 male) who underwent vaccination with two doses of CoronaVac and BNT162b2 booster after 6-months of primary protocol. Findings: Elevated levels of anti-spike IgG antibodies were detected after CoronaVac vaccination, which significantly decreased after 80 days and remained stable until the introduction of the booster dose. Heterologous booster restored antibody titers up to-1·7-fold, changing overall seropositivity to 96%. Titers of neutralising antibodies to the Omicron variant were lower in all timepoints than those against Delta variant. Individuals presenting neutralising antibodies against Omicron also presented the highest titers against Delta and anti-Spike IgG. Cellular immune response measurement pointed out a mixed immune profile with a robust release of chemokines, cytokines, and growth factors on the first month after CoronaVac vaccination followed by a gradual reduction over time and no increase after the booster dose. A stronger interaction between those mediators was noted over time. Prior exposure to the virus leaded to a more robust cellular immune response and a rise in antibody levels 60 days post CoronaVac than in individuals with no previous COVID-19. Both vaccines were safe and well tolerated among individuals. Interpretation: Our data approach the effectiveness of CoronaVac association with BNT162b2 from the clinical and biological perspectives, aspects that have important implications for informing decisions about vaccine boosters.